2012
DOI: 10.1371/journal.pone.0045147
|View full text |Cite
|
Sign up to set email alerts
|

Western Australian Marsupials Are Multiply Infected with Genetically Diverse Strains of Toxoplasma gondii

Abstract: Five different organs from 16 asymptomatic free-ranging marsupial macropods (Macropus rufus, M. fuliginosus, and M. robustus) from inland Western Australia were tested for infection with Toxoplasma gondii by multi-locus PCR-DNA sequencing. All macropods were infected with T. gondii, and 13 had parasite DNA in at least 2 organs. In total, 45 distinct T. gondii genotypes were detected. Fourteen of the 16 macropods were multiply infected with genetically distinct T. gondii genotypes that often partitioned between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 27 publications
1
47
0
2
Order By: Relevance
“…Many RT-qPCR assays have been developed, for example for the fish parasites Ichthyobodo and Ichthyophonus [57,58], the myxozoan parasite Ceratonova (previously Ceratomyxa) shasta in rivers [59], screening marsupials for Toxoplasma gondii [60], and monitoring of intranuclear coccidian parasites in endangered turtles [61]. For very well studied groups or systems, such as Cryptosporidium, Giardia, and Enterocytozoon, the molecular tools have become diverse and refined; for example, allowing identification of differently distributed genetic subtypes in wastewater samples [62] and using quantification to estimate transmission risk [63].…”
Section: Targeted Molecular Approaches Edna and Insights Into Life mentioning
confidence: 99%
“…Many RT-qPCR assays have been developed, for example for the fish parasites Ichthyobodo and Ichthyophonus [57,58], the myxozoan parasite Ceratonova (previously Ceratomyxa) shasta in rivers [59], screening marsupials for Toxoplasma gondii [60], and monitoring of intranuclear coccidian parasites in endangered turtles [61]. For very well studied groups or systems, such as Cryptosporidium, Giardia, and Enterocytozoon, the molecular tools have become diverse and refined; for example, allowing identification of differently distributed genetic subtypes in wastewater samples [62] and using quantification to estimate transmission risk [63].…”
Section: Targeted Molecular Approaches Edna and Insights Into Life mentioning
confidence: 99%
“…As with Trichinella, research over the last decade has demonstrated that Toxoplasma is far more prevalent in wildlife than previously considered, and affects a huge diversity of species, both terrestrial and marine mammals and birds, in all environments studied including the Arctic (Wendte et al, 2011;Pan et al, 2012;Jenkins et al, 2013). In addition, as more isolates from wildlife are characterised genetically using multiple loci, what is also apparent is the great genetic diversity of Toxoplasma in wildlife and the occurrence of novel genotypes which differ from the 'standard' domestic strains (Ajzenberg et al, 2004;Wendte et al, 2011;Pan et al, 2012). These observations raise many questions about the ecology of Toxoplasma infections in wildlife ecosystems and how it differs from that in domestic ecosystems from which we have obtained most of the information on which we have based our understanding of the population dynamics and transmission.…”
Section: Toxoplasmamentioning
confidence: 99%
“…Firstly, little is known about the virulence of strains of Toxoplasma that are maintained in wildlife populations. Available evidence would suggest that they are largely avirulent in natural ecosystems (Thompson et al, 2010a;Pan et al, 2012). Toxoplasma is prevalent in wildlife ecosystems and exhibits a high level of genetic variation.…”
Section: Toxoplasmamentioning
confidence: 99%
See 1 more Smart Citation
“…Australia [55] Red Kangaroo Macropus rufus Toxoplasma gondii Australia [60] Eimeria toganmainensis Australia [59] Eimeria wilcanniensis Australia [59] Eimeria macropodis Australia [59] Leishmania spp Australia [61] Western grey kangaroo…”
Section: Continued Eimeria Toganmainensismentioning
confidence: 99%